Analysis Of The Impact Of The Covid-19 Pandemic On Online Learning In Elementary School - Lulu Syarifatul Munawaroh; Ima Rismayanti; Siti Sahronih; hamad Guntur (Journal Of Social Science (JoSS), 2022)
This study aims to analyze online learning at home for elementary school students the impact of the COVID-19 pandemic. The research uses a literature study method, where in collecting data information with documentation techniques, namely looking for data on relevant matters from various sources in the library such as documents, books, magazines, news and journals. The criteria for the sources chosen were discussions about the impact of the COVID-19 pandemic and online learning in elementary schools. From the sources obtained, the most relevant are then selected. The results in the study show that there are many impacts of the COVID-19 pandemic on online learning in elementary schools. This can be seen from the results of the data obtained showing that due to the COVID-19 pandemic it has an impact on students, parents, and teachers but can be carried out quite well if there is cooperation between teachers, students, and parents while studying at home